If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 4 = -5x + -7 Reorder the terms: 4 + X = -5x + -7 Reorder the terms: 4 + X = -7 + -5x Solving 4 + X = -7 + -5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + X = -7 + -4 + -5x Combine like terms: 4 + -4 = 0 0 + X = -7 + -4 + -5x X = -7 + -4 + -5x Combine like terms: -7 + -4 = -11 X = -11 + -5x Simplifying X = -11 + -5x
| 6x+8=8-x | | 7(Y-1)=-42 | | 3(4-a)=2(a+6) | | -13(n+20)=(-11n+38) | | 0=9x^2-2kx+3k | | 9-x*1/2=13 | | 24=2/3V | | 5/12/360 | | -2x-3y=-30 | | 2.25+3.50x=44.25 | | 360/6x | | 2(10x-5)=4(5x+2) | | 14p+20q+p-7q-3p= | | 44.25=2.25+3.50x | | 6/7=3V | | 2-3(y-5)=3+(y+1) | | 4z+6= | | 2t-4s-2t+4s= | | (4b+7)-(6b-3)= | | 12=n-10 | | -x-5y=-54 | | 6x-12=3610x | | f(x)=-0.04x^2+0.8x | | 5(3e+2e-g)= | | 4s+5+5s-5= | | 3m-500=356 | | 2-4x=-7-1x | | 3a+ap=4p | | 3j=-2j+6 | | 2x-xy+y+5=0 | | 9m+8=88 | | -6x+4c-7x=0 |